(untitled) (SCIENCE TIME JOURNAL, 2026)
This article analyzes the main difficulties encountered in translating cultural references in the process of simultaneous interpretation. The correct translation of elements such as cultural information, historical events, national values, jokes, expressions and metaphors requires simultaneous interpreters not only high language competence, but also deep cultural knowledge and quick thinking. The article highlights the problems of loss of meaning in different cultural contexts, cultural inconsistency, and adequate communication of information to the listener.